Back to the future? The role of temporal focus for mapping time onto space. Issue 2 (February 2020) - Bylund, Emanuel; Gygax, Pascal; Samuel, Steven; Athanasopoulos, Panos
Do we conceptualise the future as being behind us or in front of us? Although this question has traditionally been investigated through the lens of spatiotemporal metaphors, new impetus was recently provided by the Temporal-Focus Hypothesis. This hypothesis holds that the mapping of temporal concepts onto the front–back axis is determined by an individual's temporal focus, which varies as a function of culture, age, and short-term attention shifts. Here, we instead show that participants map the future on to a frontal position, regardless of cultural background and short-term shifts. However, one factor that does influence temporal mappings is age, such that older participants are more likely to map the future as behind than younger participants. These findings suggest that ageing may be a major determinant of space–time mappings, and that additional data need to be collected before concluding that culture or short-term attention do influence space–time mappings.